Case report of ervical myelopathy due to ossification of the posterior longitudinal ligament in association with flavum ligament ossification: MRI and CT appearance - Boukobza, Monique; Ušinskienė, Jurgita; Letautienė, Simona (Acta medica Lituanica, 2013)
Background. Our objective is to analyze the cervical spinal cord damage and spinal canal stenosis due to OPLL which usually affects the cervical spine and leads to progressive myelopathy in 50–60s in Asian population; to demonstrate the mixed type OPLL and to show OPLL specific dural penetration signs: “double- layer” and “C-sign” on imaging. Materials and methods. Subacute cord compression developed over a 3-month period in a 43-year-old Japanese patient. Severe spinal canal narrowing was related to the mixed type OPLL at C3–C4 through C6–C7 associated to flavum ligament ossification at T3–T4. Lateral radiograph of the cervical spine showed intraspinal ossification, CT demonstrated specific dural penetration signs, and MRI disclosed spinal cord compression. Laminectomy at C3–C7 was performed and decompression of the spinal cord was confirmed by postoperative MRI. Conclusions. Absolute cervical stenosis and association with other diseases (like calcification of flavum ligament) predispose the patient to develop more severe deficit earlier in the clinical course. Specific CT signs, “double-layer” and “C-sign”, show dural involvement. MRI is a very useful modality to identify the precise level and extent of the spinal cord injury. OPLL must be included in the differential diagnosis of subacute cervical myelopathy.